2019
DOI: 10.1111/bjh.15875
|View full text |Cite
|
Sign up to set email alerts
|

A Toll‐like receptor 2 genetic variant modulates occurrence of bacterial infections in patients with sickle cell disease

Abstract: Summary Despite adequate immunization and penicillin prophylaxis, bacterial infections remain a leading cause of morbidity and mortality in patients with sickle cell disease (SCD). Besides hyposplenism, inflammatory and genetic factors might modulate their susceptibility to bacterial infections. We performed a candidate gene association of single nucleotide polymorphisms (SNPs) located in Toll‐like receptor (TLR) genes, encoding prominent molecules for innate immune responses, with the occurrence of bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…This explains why comparisons between SCD and non-SCD populations, and among SCD patients, may uncover different effects of a given SNP—for instance, alleles and genotypes that modify the function of TLR and modulate the occurrence of infections in this population. Based on our findings and in previous studies on the functional role of this SNP ( 15 , 51 56 ), we hypothesized that TA genotype might determine a balanced inflammatory response, whereas the TT genotype would determine a weak inflammatory response, and the AA genotype, an overwhelming inflammatory response pattern. Further studies assessing the role of this SNP and its protein expression are required in SCD settings.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…This explains why comparisons between SCD and non-SCD populations, and among SCD patients, may uncover different effects of a given SNP—for instance, alleles and genotypes that modify the function of TLR and modulate the occurrence of infections in this population. Based on our findings and in previous studies on the functional role of this SNP ( 15 , 51 56 ), we hypothesized that TA genotype might determine a balanced inflammatory response, whereas the TT genotype would determine a weak inflammatory response, and the AA genotype, an overwhelming inflammatory response pattern. Further studies assessing the role of this SNP and its protein expression are required in SCD settings.…”
Section: Discussionmentioning
confidence: 52%
“…Of note, the TLR2 rs4696480 TA genotype was significantly associated with occurrence of 0-1 clinical complications. Previously, our group has found that the same genotype was associated with less bacterial infections in SCD (15). Patients with SCD exhibit a marked susceptibility to infections, compared with non-SCD individuals, due to several factors, such as loss of spleen function and the chronic inflammatory status (50).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations